The Practice of Buying Pineapple Fruit in Packages From a Sharia Economic Perspective. - Sukiran, Sukiran; Nurjali, Nurjali (Zabags International Journal of Economy, 2023)
The research in this scientific work aims to find out what the practice of buying and selling sacked pineapples is in Jati Mulyo Village, Dendang District, and whether the buying and selling practices are in accordance with sharia economic perspectives. This research is qualitative field research, data collection for this research was carried out by conducting observations and interviews, with the research object being pineapple traders in Jati Mulyo Village, Dendang District regarding the practice of buying and selling sacked pineapples in Jati Mulyo Village, Dendang District from an economic perspective. Sharia. The author also conducted research (library research). The results of this research found that the practice of buying and selling pineapples in Jati Mulyo Village, Dendang District is based on the prices prevailing on the market and the prices prevailing at that time, then what differentiates the prices between traders is where the pineapple supply comes from. From a sharia economic perspective, the price differences in buying and selling pineapples in Jati Mulyo Village, Dendang District as a whole are in accordance with the concept of price in a sharia economic perspective, so that harmony and conditions in buying and selling pineapples have also been fulfilled because the prices set do not harm buyers, namely traders. pineapple takes profits at a reasonable level. Then regarding marketing, it meets marketing requirements because there is transparency and there is no coercion on consumers because consumers shop only according to quality and their needs. Meanwhile, in terms of the practice in marketing pineapples, it is in accordance with sharia because it meets the requirements of buying and selling in Islam, namely, being honest in buying and selling, being fair in selling pineapples, such as not differentiating between one consumer and another, being of low service. heart.